2015
DOI: 10.1128/jvi.02370-14
|View full text |Cite
|
Sign up to set email alerts
|

Short Conserved Sequences of HIV-1 Are Highly Immunogenic and Shift Immunodominance

Abstract: HIV-1 sequence diversity is a major barrier limiting the capability of cellular immunity to contain infection and the ability of vaccines to match circulating viral sequences. To date, vaccines tested in humans have delivered whole proteins or genes for whole proteins, and it is unclear whether including only conserved sequences would yield sufficient cellular immunogenicity. We tested a vaccine delivering genes for four small conserved HIV-1 regions compared to a control vaccine with genes for whole Gag, Env,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…In contrast, CD8+ T-cell-directed vaccines can target more conserved protein regions with greater cross-reactive potential and for which escape has greater fitness costs; [16][17][18][19][20][21][22][23][24][25] moreover, vaccination can shift responses toward highly conserved epitopes that are infrequently presented in natural infection, which may be advantageous in a therapeutic setting. 16,18,24,26 In addition, a new type of T-cell-based vaccine modality is being explored based on the observation that non-classical MHC-E restricted CD8+ T-cell responses elicited by SIV antigens delivered in a modified cytomegalovirus vector can clear SIV infections in over half of vaccinated macaques in an SIV challenge model.…”
Section: A Case For a Multicomponent Hiv Vaccinementioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, CD8+ T-cell-directed vaccines can target more conserved protein regions with greater cross-reactive potential and for which escape has greater fitness costs; [16][17][18][19][20][21][22][23][24][25] moreover, vaccination can shift responses toward highly conserved epitopes that are infrequently presented in natural infection, which may be advantageous in a therapeutic setting. 16,18,24,26 In addition, a new type of T-cell-based vaccine modality is being explored based on the observation that non-classical MHC-E restricted CD8+ T-cell responses elicited by SIV antigens delivered in a modified cytomegalovirus vector can clear SIV infections in over half of vaccinated macaques in an SIV challenge model.…”
Section: A Case For a Multicomponent Hiv Vaccinementioning
confidence: 99%
“…51 Vaccines with improved antigen design and delivery strategies can elicit higher numbers of responses 38,55 with greater crossreactive potential. 17,19,21,24,25,56 Furthermore, NHP SIV challenge studies have repeatedly found that CD8+ T-cell responses, particularly those targeting Gag, directly correlate with better viral control and survival. [57][58][59][60][61][62][63] Vaccine antigen designs to elicit enhanced CD8+ T-cell immune and humoral responses…”
Section: Vaccine-induced Cd8+ T-cells Responses Associated With Protementioning
confidence: 99%
See 3 more Smart Citations